Clinical outcomes in hybrid repair procedures for pathologies involving the aortic arch. (February 2015) - Zerwes, Sebastian; Leissner, Giesbert; Gosslau, Yvonne; Jakob, Rudolf; Bruijnen, Hans-Kees; Oertl, Frank; Woelfle, Klaus
Objective: Fifty patients with complex aortic disease, who received hybrid treatment of the aortic arch with supra-aortic debranching and endovascular stent-graft repair, were evaluated in regard to events of primary (survival and technical success) and secondary (procedure-related complications) interest. Methods: The single-center study was conducted over an eight-year period from December 2004 to December 2012. Treated medical conditions included 23 aortic aneurysms (46%), 21 aortic dissections (42%), and six penetrating aortic ulcers (12%). Procedures were divided into groups of elective, urgent, and emergent. Results: Twenty-eight (56%) patients were operated electively, 15 (30%) urgently, and seven (14%) emergently. Sternotomy, cardiopulmonary bypass, and deep hypothermic circulatory arrest were required in 12 (24%) patients. The primary technical success rate was 86% and raised to 92% ( n  = 46) of secondary technical success rate after therapy of three type I endoleaks. The 30-day mortality added up to 16.0%, and the mean time of survival was 49.3 months. In a total of eight (16%) patients, an endoleak occurred (five endoleaks type I, three endoleaks type II), while nine (18%) of patients suffered a perioperative stroke. Conclusions: In severely ill patients with complex aortic diseases, hybrid therapy may offer a promising alternative to conventional open repair.